Inovasi Financial Technology (Fintech) dalam Meningkatkan Efisiensi Layanan Asuransi Syariah di Era Digital - Muhammad Zainuddin Azi; Muhammad Ikhsan Harahap; Nurul Inayah (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to examine the implementation of Financial Technology (Fintech) innovations in the development of sharia insurance services at PT Jiwasraya. In a rapidly evolving digital era, the integration of fintech has become a crucial strategy to enhance efficiency, transparency, and the outreach of insurance services based on sharia principles. This research adopts a qualitative approach using a case study method at PT Jiwasraya. Data collection techniques include in-depth interviews, documentation, and literature studies. The findings indicate that fintech innovations implemented at the company include the digitalization of policy services, online premium payments, and the use of artificial intelligence (AI) for risk analysis and customer service. The application of these technologies not only accelerates business processes but also increases customer trust in a more modern and transparent sharia financial system. It can be concluded that fintech plays a strategic role in driving the sustainable and competitive transformation of sharia insurance services in the digital age. The development of sharia insurance in Indonesia has shown significant growth in recent years. This is marked by an increasing number of sharia insurance companies, both as independent entities and as sharia business units of conventional insurance firms. Growing public awareness of the importance of financial protection aligned with sharia principles has also fueled the demand for insurance products based on the concepts of mutual help (ta'awun) and donation (tabarru'). On the other hand, regulatory support from the Financial Services Authority (OJK) and ongoing efforts to improve sharia financial literacy have also played a crucial role in driving the growth of this sector.